Baseline Mood-State Measures as Predictors of Antidepressant Response to Scopolamine - Furey, Maura L. (2012)
Identifying predictors of antidepressant response will facilitate the successful treatment of patients suffering from depression. Scopolamine produces robust antidepressant responses in unipolar and bipolar depression. Here we evaluate the potential for baseline self-ratings to predict treatment response to scopolamine. Fifty-one unipolar and bipolar patients participated in a double-blind, placebo-controlled crossover trial. Following a single-blind placebo session, participants randomly received P/S or S/P (P=3 placebo; S=3 scopolamine (4ug/kg) sessions). Mood-state self-ratings (POMS and VAS) and depression severity (MADRS) were obtained before each infusion. Day 1 (baseline/placebo) self-ratings were used in a discriminant function analysis to identify linear combinations of individual items that predict response. The discriminant analysis separated responders from non-responders in both the unipolar (Chi-square=22.6, p=0.002) and bipolar (Chi-square=11.2, p=0.025) diagnostic subgroups. The discriminant functions accurately classified over 85% of patients as responders/non-responders. The POMS depression subscale correlated with clinical response (r=-.47; p<0.001), as did the VAS restlessness (r=-.49; p<0.001), sad (r=-.49, p<0.0001) and irritated (r=-.40, p=0.004) scales. These results indicate that self-report mood-ratings obtained prior to treatment can predict response outcome to scopolamine, and suggest that a constellation of mood-state features may be related to clinical response.